A Clinical and Radiological Investigation of the Use of Dermal Fat Graft as an Interpositional Material in Temporomandibular Joint Ankylosis Surgery. Issue 1 (March 2020) - Rahman, Sajjad Abdur; Rahman, Tabishur; Hashmi, Ghulam Sarwar; Ahmed, Syed Saeed; Ansari, Mohammad Kalim; Sami, Abdus
Management of temporomandibular joint (TMJ) ankylosis is mainly through surgical intervention. Interpositional materials are a necessity when it comes to prevention of TMJ re-ankylosis after arthroplasty. Early aggressive postoperative physiotherapy is essential for the prevention or treatment of TMJ hypomobility or ankyloses. Recently, it has been shown that abdominal dermis fat helps promote smooth, pain-free joint function and it is stable after interposition and less prone to fragmentation. The purpose of this study was to assess that whether dermal fat is a good choice of interpositional material when it comes to decreased pain perception during aggressive physiotherapy after release of ankyloses thus ensuring good compliance by the patient. We also assessed the fate of the graft material on computed tomography to evaluate any volume changes if occurred after interposition.